MR imaging of anterio cruciate ligament injuries - Chaudhari, Nilesh H.; Bagga, Rounak R.; Patni, Zoya M. (International Journal of Research in Medical Sciences, 2017)
Background: Of all the ligaments of the knee joint the Anterior cruciate ligament (ACL) is the most commonly injured. It is an important pillar of the ligament stabilization of knee joint preventing anterior translation of Tibia over Fibula. Magnetic resonance imaging (MRI) is an excellent modality providing fine-resolution and multiplanar imaging without any radiation, for detection and evaluation of ACL injury with the associated injuries to other ligaments of the knee join. The purpose of the work was to study the role of MRI in classifying the ACL injuries. Methods: MRI Knee of 162 patients with ACL injuries was studied. All the MR imaging scans were performed on 1.5-T MR system (Siemens magnetom Essenza). Results: A total of 162 patients were studied in which majority of them i.e. 43 patients had interstitial sprain, 38 patients had complete tear, 33 patients had mucoid degeneration, 27 had partial tear and 14 had high grade partial tear, however 7 patients had normal ACL. There were associated injuries to the other ligaments of the knee joint along with ACL injury, medial meniscus tear being the most common and was seen in 39.50% followed by lateral meniscus tear in 9.87%, MCL tear in 6.79%, LCL tear in 1.85% and PCL tear in 2.46 %. Conclusions: MRI is a good modality for classifying ACL injury and evaluation of injuries to the associated ligaments.